On the Edge of Mathematics and Biology Integration: Improving Quantitative Skills in Undergraduate Biology Education - Feser, Jason (American Society for Cell Biology, 2013)
The feature describes two major efforts to integrate mathematics and biology. A call is made to biologists to consider the need to address biology undergraduate education changes and to use the resources described.